2005
DOI: 10.1002/chin.200552212
|View full text |Cite
|
Sign up to set email alerts
|

Present and Future Applications of Carbon Nanotubes to Analytical Science

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…Carbon nanotubes (CNTs) continue to receive remarkable attention in electrochemistry [25][26][27][28][29][30][31]. Since its discovery by Iijima [32] in 1991 using transmission electron microscopy, CNTs have been the subject of numerous investigations in chemical, physical and materials areas due to their Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) continue to receive remarkable attention in electrochemistry [25][26][27][28][29][30][31]. Since its discovery by Iijima [32] in 1991 using transmission electron microscopy, CNTs have been the subject of numerous investigations in chemical, physical and materials areas due to their Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Both types of CNTs have many potential applications in various industrial areas in large volumes: e.g., in nanocomposites for sporting materials, as battery electrodes, in supercapacitors, transparent films and liquid crystal displays. Other limited-volume applications include their use as components in wind turbine blades, scanning probe tips, membrane filters and sorbents, flat panel displays, memory devices, hydrogen-storage electrodes, biosensors, multitip array X-ray sources, transistors, drug delivery systems, as well as other medical and analytical chemistry applications [2,3]. The demand created by these applications has led to significant growth in the global market for CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental and theoretical studies reported that amongst the nucleotides, adenine base has the highest affinity to gold particles [9] and preferentially binds to a nitrogen atom at the N7 position [10]. Furthermore, there is considerable interest in applying carbon nanotubes (CNTs) as charge-transport centers for electronic transducers [11][12][13][14][15]. Hence, several experiments have focused on the deposition of Au NPs onto CNTs [16][17][18][19] and there is increasing attraction to exploit a compatible assembly of them as nanoscale building-blocks for DNA detection [20].…”
Section: Introductionmentioning
confidence: 99%